Reliability of recommended non-invasive chairside screening tests for diabetes-related peripheral neuropathy: a systematic review with meta-analyses. Issue 2 (24th December 2021) - McIllhatton, Ally; Lanting, Sean; Lambkin, David; Leigh, Lucy; Casey, Sarah; Chuter, Vivienne
Abstract : The objective is to determine, by systematic review, the reliability of testing methods for diagnosis of diabetes-related peripheral neuropathy (DPN) as recommended by the most recent guidelines from the International Diabetes Foundation, International Working Group on the Diabetic Foot and American Diabetes Association. Electronic searches of Cochrane Library, EBSCO Megafile Ultimate and EMBASE were performed to May 2021. Articles were included if they reported on the reliability of recommended chairside tests in diabetes cohorts. Quality appraisal was performed using a Quality Appraisal of Reliability Studies checklist and where possible, meta-analyses, with reliability reported as estimated Cohen's kappa (95% CI). Seventeen studies were eligible for inclusion. Pooled analysis found acceptable inter-rater reliability of vibration perception threshold (VPT) (κ=0.61 (0.50 to 0.73)) and ankle reflex testing (κ=0.60 (0.55 to 0.64)), but weak inter-rater reliability for pinprick (κ=0.45 (0.22 to 0.69)) and 128 Hz tuning fork (κ=0.42 (0.15 to 0.70)), though intra-rater reliability of the 128 Hz tuning fork was moderate (κ=0.54 (0.37 to 0.73)). Inter-rater reliability of the four-site monofilament was acceptable (κ=0.61 (0.45 to 0.77)). These results support the clinical use of VPT, ankle reflexes and four-site monofilament for screening and ongoing monitoring of DPN as recommended by the latest guidelines. The reliability of temperature perception, pinprick, proprioception, three-site monofilament and Ipswich touch test when performed in people with diabetes remains unclear.